Perceptions of barriers to and facilitators of physical activity in adults with cystic fibrosis. (2nd January 2023) - Ladune, Raphaëlle; Filleul, Valentine; Falzon, Charlène; Hayotte, Meggy; Mély, Laurent; Vallier, Jean-Marc; Gruet, Mathieu; Vuillemin, Anne; d'Arripe-Longueville, Fabienne
ABSTRACT: Background: Physical activity (PA) is a proven therapeutic tool to increase the quality of life and life expectancy in people with cystic fibrosis (pwCF). Despite this, the PA level of pwCF is lower than recommended. Objectives: This study was conducted to identify the barriers to and facilitators of PA in adults with CF with heterogeneous severity. Methods: Twenty adults with CF (mean age = 33.3±11.7 years, mean FEV1% = 50.55±20.4%) were recruited from two specialized centers and interviewed about the factors that limit and facilitate their PA. The collected data were transcribed, coded and analyzed using deductive and inductive methods. Results: Barriers and facilitators were classified into physical, psychological and environmental dimensions. The main barriers were fatigue, breathing difficulties, lack of available facilities, negative perceptions of PA and perceived health risks. The most important facilitators were respiratory benefits, well-being, and social support. Conclusion: Although some barriers and facilitators were similar to those found in children with CF or adults from other vulnerable populations, others were specific to adults with CF, such as the risk of cross-contamination and transplant preparation. The comprehensive study of the barriers and facilitators in adults will enhance PA counseling for pwCF and help improve their compliance with PA recommendations.